A Qualitative Phenomenological Study of Perinatal Loss Experiences in Indonesia: A Trauma-Informed Care Perspective - Evi Wahyuntari; Cesa Septiana Pratiwi; Ellyda Rizki Wijhati; Oktavianus Wahyu Prihantoro Trisno Putro (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Perinatal loss is a profound health event that extends beyond medical complications and encompasses emotional, social, and spiritual consequences for the women and their families. This study aimed to explore the experiences of women, their partners, and healthcare providers. In many setting, care following perinatal loss remains primarily biomedical, with limited attention to psychosocial and bereavement needs. This study aimed to explore how women, their partners and healthcare professionals’ experience and engage with perinatal loss in Indonesia and to provide recommendations for more holistic and responsive maternal healthcare services. Methods: A qualitative phenomenological design was conducted between June and September 2025 in Yogyakarta and Central Java, Indonesia. A total of 27 participants were recruited, including 11 women who experienced perinatal loss, 7 husbands, and 9 healthcare providers (midwives and general practitioners). Data were collected through in-depth interviews and focus group discussions and analysed thematically using Braun and Clarke’s six-step approach, guided by Trauma-Informed Care principles. Ethical approval was secured from the Health Research Ethics Committee of Universitas ‘Aisyiyah Yogyakarta. Results: The analysis identified four overarching themes: pregnancy journey and risks, healthcare services experiences, spiritual coping and grief after perinatal loss and bereavement care and institutional support. Participants described delayed risk recognition, inconsistent referral pathways and communication that priorities clinical information over emotional support. Mothers reported prolonged grief, guilt and spiritual searching, while fathers often experienced hidden distress and emotional suppression. Healthcare providers acknowledged emotional burden, limited training and the absence of structured bereavement protocols. Conclusion: Perinatal loss care in Indonesia requires strengthening through trauma-informed approaches that integrate emotional, spiritual and social dimensions alongside clinical management. Developing consistent bereavement protocols and providing equitable psychosocial support for mothers and fathers are essential to improve family wellbeing and system responsiveness.